Miss-represented - Pontsho Pilane; Mehita Iqani (Communicare)
This paper reports on a quantitative content analysis of 2,699 images of women present in one year’s worth of the South African edition of Glamour magazine. Motivated by critical race theory, black feminist thought and critical consumption studies, the aim of the study was to determine how often black women were represented in the sample and, further, to examine the particular body types and hairstyles preferred in the aesthetic of black women featured. The findings showed that even though Glamour magazine claims that 65% of its readership is comprised of black women, they feature in only 30% of images, and when present, have hairstyles and body types most commonly associated with white supremacist ideas of beauty. The (albeit unsurprising) failure of Glamour magazine to adequately represent a diversity of black femininities is theorised as a result of pervasive neo-liberal, racist and patriarchal structures of power in post-apartheid South Africa. We argue that the case study illuminates a racially charged post-feminist moment, in which black women are represented as valuable only in terms of their proximity to a white ideal, and valued only in terms of their lucrative potential as an aspirant, compliant mass market.